Anatomy‐guided injections of botulinum neurotoxin in neck muscles: how accurate is needle placement?. (19th July 2020) - Kreisler, A.; Simonin, C.; Degardin, A.; Mutez, E.; Defebvre, L.
Abstract : Background and purpose: In cervical dystonia, the accuracy of botulinum neurotoxin (BoNT) injections may influence the response to the treatment. Methods: We used ultrasound to evaluate the accuracy of anatomy‐guided injections of BoNT in the neck muscles. Results: A total of 56 consecutive patients and 332 injections were evaluated. The overall accuracy was 76.6%. The lowest accuracy (67.9%) was observed for the splenius capitis muscle. Conclusions: Anatomic guidance of BoNT injections in the neck muscles is often inaccurate. Imaging guidance may improve the accuracy of BoNT injections in cervical dystonia.